Three new species of Cirrothaumatia Razowski & Becker from Peru, with notes on the genus (Lepidoptera: Tortricidae: Tortricinae: Cochylini) - Heppner, John B.; Bae, Yang-Seop (Zootaxa, 2024)
Three new species of the cochyline genus Cirrothaumatia Razowski & Becker, 1986 are described and illustrated from submontane Andean sites in Peru (Depts. Amazonas, Junín, and San Martín): C. pichita n. sp., C. huemboana n. sp., and C. moyobamba n. sp. Comments and illustrations are provided for the three previously described species from southern Mexico (Veracruz), Central America (Guatemala, Costa Rica, and Panama), and northern South America (Venezuela: Edo. Aragua; Ecuador: Pichincha Prov.).